Importance of Innovative Technologies in Mathematics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, scientific opinions about the importance of innovative technologies in mathematics are presented and their role in improving the methodological work of mathematics education is revealed. Interactive strategies of mathematics education based on modern pedagogical technologies facilitate the educational process, clarify it, and cover a wide community. intended.